Sequential use of double-balloon catheter and oral misoprostol versus oral misoprostol alone for induction of labour at term (CRBplus trial): a multicentre, open-label randomised controlled trial - Kehl, Sven; Ziegler, Julia; Tuschy, Benjamin; Berlit, Sebastian; Kirscht, Jade; Weiß, Christel; Sütterlin, Marc (BJOG, 2014)
Objective: To evaluate the efficacy of inducing labour using a double-balloon catheter and oral misoprostol sequentially, in comparison with oral misoprostol alone. Design: A multicentre randomised controlled trial. Setting: Five hospitals in Germany. Population: A total of 326 pregnant women with an unfavourable cervix undergoing labour induction at term. Methods: Women were randomly assigned according to a computer-generated allocation sequence to sequential use of double-balloon catheter and oral misoprostol (study group) or oral misoprostol alone (control group). In the study group, the double-balloon catheter was used the first day before starting oral misoprostol the second day. Main outcome measures: The primary outcome measure was the induction-to-delivery interval, and a further outcome parameter was delivery within 48 hours. Results: The median times for induction of labour until delivery were 32.4 hours in the study group and 22.5 hours in the control group (P = 0.004). This difference was not seen when evaluating according to parity (nulliparous, P = 0.19; parous, P = 0.06). The rate of vaginal delivery within 48 hours did not differ between both groups. The number of applications of misoprostol (two versus three, P < 0.001) and the dose of misoprostol used was lower in the study group (100 versus 200 μg, P < 0.001). In the study group, there were more Apgar scores of <7 at 5 minutes (8 versus 1, P = 0.04). Conclusions: The use of a double-balloon catheter on the first day, before starting oral misoprostol on the second day, did not improve the induction to delivery interval and the rate of delivery within 48 hours, in comparison with oral misoprostol alone.